PALINOLOGÍA DE LA FORMACIÓN CHIQUIMIL (MIOCENO SUPERIOR) EN VALLECITO, PROVINCIA DE CATAMARCA, ARGENTINA. PARTE 1. ESPORAS: ESPECIES NUEVAS (Ameghiniana, 2014)
Two new spore species from sediments ofthe Chiquimil Formation cropping out at Vallecito, Catamarca Province are here defined. These are: Dictyophyllidites chiquimilense sp nov. and Muricingulisporis verrucosus sp. nov. Dictyophyllidites chiquimilense has a botanical affinity with the farnilies Matoniaceae or Cyatheaceae; M. verrucosus is similar to extant species of Pteris and Anogramma of the farnily Pteridaceae. This is the second species of the genus Muricingulisporis to be described from the Argentine Tertiary.